Perilaku Agresif Siswa dari Keluarga Broken Home - Pratama, Randi; Syahniar, Syahniar; Karneli, Yeni (Konselor, 2016)
This research is based because of the aggressive behavior shown by the students, especially students who come from a broken home. The purpose of this study is to describe the aggressive behavior that is owned by a student who comes from a broken home in terms of attacking people physically, verbally, and damaging and destroying property and wealth of others. The results of this research shows that in general student’s aggressivebehavior are on average level. Implications of research in guidance and counseling is as the basis for programs to prevent and cope with aggressive behavior that is owned by the students, especially students who come from a broken home. Cooperation with the homeroom teacher mentors, teachers and other school personnel will also help identify students who have an aggressive behavior, especially students who come from a broken home to immediately provided services.